Sustainable development challenges in Indonesia: A macroeconomics approach to finance, energy, and environment - Muhammad Firmansyah; Immanuel Mu’ammal; Stanislaw Flejterski; Jose Antonio Lopez Castro (Universitas Ahmad Dahlan, 2026)
This study aims to examine the relationships among credit dynamics, foreign direct investment, energy, economic growth, and environmental degradation in Indonesia from 1990 to 2024. Using a quantitative path analysis, this study examines the direct and indirect effects of working capital credit, consumer credit, foreign direct investment (FDI), and electricity consumption on environmental degradation via economic growth. The results reveal that all variables have a positive and significant effect on economic growth, with electricity consumption (β = 0.361; p < 0.007) being the primary contributor. Economic growth and electricity consumption also significantly increase environmental degradation, supporting the Environmental Kuznets Curve (EKC) hypothesis in Indonesia. Moreover, the analysis of indirect effects shows that economic growth mediates the relationships among credit distribution, FDI, and environmental degradation. This research is important because it examines sustainable development in Indonesia, where economic growth driven by the financial sector, FDI, and electricity consumption could increase carbon emissions and environmental degradation. These findings are relevant because they provide empirical evidence on the impact of financial and energy activities on environmental quality, both directly and through economic growth, in line with Indonesia's commitment to the SDGs and the green economy transition.